Analysis of the correlation between the clinical features of 1 865 children and adolescents with supernumerary teeth and the selection of anesthesia methods - ZHANG Yaqiu, FENG Caihua, LIANG Lirong, LIU Fei, WU Long, WANG Peijuan, GAO Zhenzhen, LIU Bing (口腔疾病防治)
Objective To retrospectively analyze the epidemiological characteristics of supernumerary teeth in patients aged 4-18 years old and the influencing factors on the selection of anesthesia methods, and to provide a reference for the selection of anesthesia plans for children and adolescents with supernumerary teeth. Methods This study is a retrospective study approved by the Institutional Ethics Committee. Based on clinical electronic medical record system and cone beam CT (CBCT) data, a retrospective analysis was conducted on 2 210 patients 4-18 years of age who underwent supernumerary tooth extraction at the School of Stomatology, Fourth Military Medical University from August 2019 to July 2021. Inclusion criteria: ① Age 4-18 years old; and ② The American Society of Anesthesiologists (ASA) classifies anesthesia into grades I-II; and ③ Have complete oral and anesthesia case records and relevant imaging data. Exclusion criteria: ① Incomplete medical records or unclear imaging data; and ② Patients with ASA grade II or above. Patients’ gender and age, the number of supernumerary teeth, arch, location, orientation, eruption status, reason for appointment, anxiety level, degree of cooperation, anesthesia method, and other relevant information were collected and statistically analyzed. Results A total of 1 865 eligible patients were included, with an average age of (8.9±3.2) years old. There were more male patients (71.37%, 1 331 cases) than female patients (28.63%, 534 cases) (P < 0.001), with a gender ratio of 2.49:1. The majority of supernumerary teeth were single (75.97%, 1 417/1 865), primarily located in the maxilla (97.2%, 1 812/1 865) and the anterior dental region (94.2%, 1 757/1 865), and in a centric position (77.3%, 1 442/1 865). The majority of patients with erupted supernumerary teeth were active in seeking treatment (97.67%, 335/343). Patients with supernumerary teeth located in the maxilla and mandible bones, as well as in the nasal floor, were mainly referred to the department for diagnosis, accounting for 94.38%(1 361/1 442) and 90.00% (72/80) (χ2=1 363.24, P < 0.001), respectively. Regarding anesthesia methods, the largest proportion of patients received nitrous oxide sedation-assisted local anesthesia or nerve block anesthesia, accounting for 38.07% (710/1 865), followed by local anesthesia, accounting for 35.23% (657/1 865). The proportion of patients receiving midazolam intravenous sedation with local anesthesia or nerve block anesthesia and general anesthesia was relatively small, accounting for 20.86% (389/1 865) and 5.84% (109/1 865). Patients 13-18 years of age with supernumerary teeth in the mandibular and posterior regions and without anxiety had the highest proportion of local anesthesia use (P < 0.001). In contrast, patients who had supernumerary teeth located at the base of the nose (50%), severe anxiety (94.12%), and poor cooperation (98.18%) had the highest proportion of general anesthesia use (P < 0.001). There was no significant difference (P = 0.35) in the incidence of intraoperative and postoperative complications after the extraction of supernumerary teeth. However, the proportion of anesthesia-related complications, such as dizziness, coughing, and respiratory depression, occurring in patients who received general anesthesia was higher than local anesthesia, accounting for 3.81% (P = 0.006). Conclusion There is a gender difference in the incidence of supernumerary teeth in patients 4-18 years of age, with a higher prevalence in males. The majority of supernumerary teeth are single and located in the maxillary anterior region, predominantly in a centric position. Patients whose teeth had erupted were more likely to seek medical treatment voluntarily, while patients with supernumerary teeth located in the maxilla and mandible bones, as well as in the nasal floor were more likely to be referred to the department. Patients with high levels of anxiety, poor cooperation, young age, multiple teeth, and high surgical difficulty were more inclined to choose general anesthesia.